2010
DOI: 10.1002/eji.200940094
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of type 1 diabetes by a new MHC II‐peptide chimera: “Single‐epitope‐mediated suppression” to stabilize a polyclonal autoimmune T‐cell process

Abstract: Polyclonality of self-reactive CD41 T cells is the hallmark of several autoimmune diseases like type 1 diabetes. We have previously reported that a soluble dimeric MHC II-peptide chimera prevents and reverses type 1 diabetes induced by a monoclonal diabetogenic T-cell population in double Tg mice [Casares, S. et al., Nat. Immunol. 2002. 3: 383-391].Since most of the glutamic acid decarboxylase 65 (GAD65)-specific CD4 1 T cells in the NOD mouse are tolerogenic but unable to function in an autoimmune environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…3B). The results indicated that, likewise the murine DEF-GAD65 reagent, [13][14][15] the human DEF-GAD65 reagent was able to stabilize the pancreatic insulitis.…”
Section: Human Def-gad65 Reagent Stabilizes the Lymphocyte Infiltratimentioning
confidence: 95%
See 3 more Smart Citations
“…3B). The results indicated that, likewise the murine DEF-GAD65 reagent, [13][14][15] the human DEF-GAD65 reagent was able to stabilize the pancreatic insulitis.…”
Section: Human Def-gad65 Reagent Stabilizes the Lymphocyte Infiltratimentioning
confidence: 95%
“…[13][14][15] Indeed, prolonged survival observed in the non responder, hyperglycemic mice treated with hu DEF-GAD65 may be explained by the formation of a protective, stabilized peri-islet pancreatic infiltration, which in turn may provide a limited, but sufficient amount of insulin to stabilize glycemia.…”
Section: Human Def-gad65 Reagent Stabilizes the Lymphocyte Infiltratimentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of dimeric pMHC have proved effective in the prevention of diabetes in spontaneous and transfer models (Masteller et al 2003;Li et al 2009;Lin et al 2010) and reversal of hyperglycemia (Casares et al 2002;Lin et al 2010). These outcomes were attributed to the generation of anergic IL-10-producing CD4 þ T cells.…”
Section: Dimersmentioning
confidence: 99%